Reaproveitamento do óleo de cozinha e fabricação do sabão caseiro - Franco , Aracelly de Oliveira; Novais, Maria Cleide Farias; Soares, Renaldo Ferreira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf